Ba AND Ni SPECIATION IN A NODULE OF BINARY Mn OXIDE PHASE COMPOSITION FROM LAKE BAIKAL - Manceau A.; Geoffroy N.; Kersten M.; Marcus M.A.; Granina L. (My University, 2007)
The partitioning and incorporation mechanism of Ni and Ba in a ferromanganese nodule from Lake Baikal were characterized by X-ray microfluorescence, microdiffraction, and absorption spectroscopy. Fe is speciated as goethite, and Mn as romanechite (psilomelane) and 10 Å-vernadite (turbostratic buserite) with minor 7 Å-vernadite (turbostratic birnessite). Barium is associated with romanechite and Ni with vernadite in distinct and irregularly distributed layers, and each type of Mn oxide is separated from the other type by goethite. The binary Mn oxide banding pattern is interpreted by a two-mode accretionary model, in which the variation in Ba flux induced by hydrothermal water pulses determines whether a tectomanganate (romanechite) or phyllomanganate (vernadite) is formed during the ferromanganese nodule accretion. Consistent with the dependence of Ni sorption on pH and the circumneutral pH of the lake water, nickel is mainly substituted isomorphically for Mn in the manganese layer, and is not sorbed at vacant Mn layer sites in the interlayer. © 2007 Elsevier Ltd. All rights reserved.